Assessment of Nursing Practice Environment and Its Influencing Factors: A Cross-Sectional Study at Shandong Province, Jinan - Zhao A; Zhang L; Shi X (Dove Medical Press, 2024)
Ailin Zhao, Li Zhang, Xiaomei Shi Department of Neurosurgery, Shandong Provincial Hospital Affiliated to Shandong First Medical University, Jinan, Shandong Province, 250001, People's Republic of ChinaCorrespondence: Xiaomei Shi, Department of Neurosurgery, Shandong Provincial Hospital Affiliated to Shandong First Medical University, No. 324 of Jing Wu Road, HuaiYin District, Jinan, Shandong Province, 250001, People's Republic of China, Tel +86 15552519354, Email shixm11xm@163.comObjective: To investigate the current nursing practice environment in Jinan, Shandong Province, and to identify the factors influencing the practice environment.Methods: This study is a cross-sectional study for nurses. From October to December 2022, using the clustering and stratified sampling methods, 2426 nurses from internal Medicine, Surgery, Obstetrics and Gynecology, Outpatient Department and Intensive Care Department of the Provincial Hospital of Shandong Medical University were selected and then investigated and analyzed using the revised Nurse Practice Environment Assessment Scale.Results: The overall mean evaluation of the practice environment scored 75.13± 19.87, with a minimum value of 59.74 and a maximum value of 95.82. The items with higher scores were "the hospital has systematic training for new nurses", "the work system is perfect", and "the hospital can provide continuing education for nurses in accordance with the needs of their positions". The items with lower scores were "nurses enjoy legal benefits", "nurses have the opportunity to participate in hospital management decisions", and "nurses have the opportunity to participate in hospital internal management". The results of the multiple linear regression analysis of the factors influencing nurses' practice environment showed that gender, education, position, and years of work were independent influences on nurses' practice environment scores (p < 0.05), and they explained 48.127% of the variation in the total scores of the nurses' practice environment scale. The estimated values (β) of sex, education, cheif nurse, nurses staff, work experience (year), and whether the only child variables were 3.141, 3.237, 2.713, 5.471, 2.074 and 0.732, respectively.Conclusion: The nurse practice environment still needs to be improved, mainly in terms of hospital management participation, human resource allocation and salary distribution system.Keywords: nurse, practice environment, cross-sectional survey, factor